A 35-year comparison of children labelled as gifted, unlabelled as gifted and average-ability - Freeman, Joan (Revista Educação Especial, 2014)
http://dx.doi.org/10.5902/1984686X14273 Why are some children seen as gifted while others of identical ability are not? To find out why and what the consequences might be, in 1974 I began in England with 70 children labelled as gifted. Each one was matched for age, sex and socio-economic level with two comparison children in the same school class. The first comparison child had an identical gift, and the second taken at random. Investigation was by a battery of tests and deep questioning of pupils, teachers and parents in their schools and homes which went on for 35 years. A major significant difference was that those labelled gifted had significantly more emotional problems than either the unlabelled but identically gifted or the random controls. The vital aspects of success for the entire sample, whether gifted or not, have been hard work, emotional support and a positive personal outlook. But in general, the higher the individual’s intelligence the better their chances in life.